2023
DOI: 10.1186/s13019-023-02144-1
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of mitral valve repair versus replacement: a propensity score analysis

Abstract: Background Mitral valve repair (MVRe) is considered to have a superior outcome compared to replacement (MVRp) in patients with mitral valve regurgitation (MVR). It was the aim of the study to analyse the clinical results and identify risk factors for short and long-term mortality. Methods In a retrospective single-center analysis, patients undergoing an isolated mitral valve procedure from June 2010 to December 2016 were identified. These were subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Most of these experiences, however, failed to characterise and analyse important factors such as patients' clinical presentation and the extension of the infective process. 2,8,10,11,12 Furthermore, in unmatched studies, mitral replacement cohorts included sicker patients who were older with a higher prevalence of active infection and heart failure and presenting with more severe lesions. 3,19,20 Not surprisingly, valve replacement is still the most common surgery for mitral valve infective endocarditis, as national registries report that mitral repair is performed in approximately 20-30% of the cases.…”
Section: Recent Cerebral Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Most of these experiences, however, failed to characterise and analyse important factors such as patients' clinical presentation and the extension of the infective process. 2,8,10,11,12 Furthermore, in unmatched studies, mitral replacement cohorts included sicker patients who were older with a higher prevalence of active infection and heart failure and presenting with more severe lesions. 3,19,20 Not surprisingly, valve replacement is still the most common surgery for mitral valve infective endocarditis, as national registries report that mitral repair is performed in approximately 20-30% of the cases.…”
Section: Recent Cerebral Strokementioning
confidence: 99%
“…There is a general tendency to offer valve repair to younger patients, with better cardiac function, a lower prevalence of severe heart failure, and often in an elective setting. In contrast, mitral valve replacement has been usually performed in acute and urgent cases with a more extensive tissue disruption 2,3,8,10–12 . Propensity-match studies have tried to overcome this limitation, but rarely were able to account for the anatomy and the extent of infective lesions.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] These studies have reported long-term mortality rates of 13-22% for patients undergoing mitral valve replacement [31][32][33] and 4-8% for patients undergoing mitral valve repair. [33][34][35] Our nding of allcause mortality seems to be in between the long-term mortality for the two different types of surgical intervention, but closer to the long-term mortality after mitral valve replacement. This matches the distribution of type of surgery, as more patients in our study group underwent mitral valve replacement (75%) than mitral valve repair (25%).…”
Section: Mortalitymentioning
confidence: 99%
“…Few studies have examined death after surgical intervention for MS alone, but multiple studies investigating mortality after surgical intervention for mitral regurgitation and MS have been conducted. [31][32][33][34][35] These studies have reported long-term mortality rates of 13-22% for patients undergoing mitral valve replacement [31][32][33] and 4-8% for patients undergoing mitral valve repair. [33][34][35] Our nding of allcause mortality seems to be in between the long-term mortality for the two different types of surgical intervention, but closer to the long-term mortality after mitral valve replacement.…”
Section: Mortalitymentioning
confidence: 99%
“…Mitral valve disease, particularly mitral regurgitation, affects a significant number of adults, making it the second most common reason for valve surgery 1 , 2 . Studies have demonstrated that mitral valve repair yields better outcomes compared to valve replacement for the treatment of mitral regurgitation 3 5 . In line with current guidelines, it is recommended to pursue early valve repair, even in the absence of symptoms, for individuals with severe mitral regurgitation at specialized heart valve centres 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%